Probing minimal supergravity at the CERN LHC for large tan beta - Baer, H.; Chen, C. H.; Drees, M.; Paige, F.; Tata, X (American Physical Soc, 1999)
For large values of the minimal supergravity model parameter tan beta, the tau lepton and the bottom quark Yukawa couplings become large, leading to reduced masses of tau sleptons and b squarks relative to their first and second generation counterparts, and to enhanced decays of charginos and neutralinos to tau leptons and b quarks. We evaluate the reach of the CERN Large Hadron Collider (LHC) pp collider for supersymmetry in the MSUGRA model parameter space. We find that values of m((g) over tilde) similar to 1500-2000 GeV can be probed with just 10 fb(-1) of integrated luminosity for tan beta values as high as 45, so that MSUGRA cannot escape the scrutiny of LHC experiments by virtue of having a large value of tan beta. We also perform a case study of an MSUGRA model at tan beta = 45 where (Z) over tilde(2)-->tau<(tau)over tilde>(1) and (W) over tilde(1)-->tau(1)nu(tau) with similar to 100% branching fraction. In this case, at least within our simplistic study, we show that a di-tau mass edge, which determines the value of m((Z) over tilde 2) - m((Z) over tilde 1), can still be reconstructed. This information can be used as a starting point for reconstructing SUSY cascade decays on an event-by-event basis, and can provide a strong constraint in determining the underlying model parameters. Finally, we show that for large tan beta, there can be an observable excess of tau leptons, and argue that tau signals might serve to provide new information about the underlying model framework. [S0556-2821(99)04205-8].